Level of nutritional knowledge and health Awareness among diabetes mellitus patients at Cheras Health Clinic, Kuala Lumpur, Malaysia - Lim, Ching Ju; Suzana Shahar; Hanis Mastura Yahya; Teh, Sin Ching; Nor Shazwani Mohd Nor; Lim, Hwa Chuo; Mohd Fauzee Mohd Zaki; Dahlia Sallehuddin; Norliza Mukhsan (Universiti Kebangsaan Malaysia, 2010)
Poor glycaemic control among diabetic patient often relates to poor nutrition knowledge. The present study investigated level of nutrition knowledge and health awareness among diabetic patients at Cheras Health Clinic. A total of 132 respondents (62 men and 70 women) were divided into two categories, adults (30 – 69 years old) (50.8%) and elderly (60 years and above) (49.2%) were involved in this research. An interview based questionnaire was used to collect data of demographic, socioeconomic, level of nutrition knowledge and health awareness. Anthropometric measurements were also recorded. The respondents consisted of 36.4% Malays, 45.5% Chinese and 18.2% Indians. Majority of the respondents had poor glycaemic control (93.6%). Overall, 37.1% respondents were categorized as having poor nutrition knowledge, followed by 31.8% moderate and only 31.1% good. Adults showed a higher (65.6 + 22.1%) nutrition knowledge score than elderly (50.5 + 22.9%) (p<0.05). Besides, respondents with formal education also showed a higher (60.7 + 22.5%) nutrition knowledge score than those without formal education (26.9 + 12.7%) (p<0.05). Majority respondents answered ‘incorrectly’ to question regarding foods to be consumed most (72.0%) and ‘did not know’ foods that were needed to repair body tissues (44.7%). Respondents who had made an effort in finding nutrition information, willing to join health program, bought health insurance and had received dietary advise showed higher nutrition knowledge score (p<0.05). In conclusion, nutritional knowledge and health awareness among diabetic patients were poor. Therefore, an intervention program and health promotion are needed to be carried out to improve health awareness and nutrition knowledge among patients with diabetis mellitus type II.